2014
DOI: 10.1016/j.rinim.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the liver-macrophages isolated from a mixed primary culture of neonatal swine hepatocytes

Abstract: We recently developed a novel procedure to obtain liver-macrophages in sufficient number and purity using a mixed primary culture of rat and bovine hepatocytes. In this study, we aim to apply this method to the neonatal swine liver. Swine parenchymal hepatocytes were isolated by a two-step collagenase perfusion method and cultured in T75 culture flasks. Similar to the rat and bovine cells, the swine hepatocytes retained an epithelial cell morphology for only a few days and progressively changed into fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…The proportion of contaminating cells that were positive for a-SMA was less than 1% by immunocytochemistry, indicating the purity of the cell population as Kupffer cells to be more than 99% (data not shown). The purity of the isolated Kupffer cells was comparable to that in the previous report (Kitani et al, 2011(Kitani et al, , 2014.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The proportion of contaminating cells that were positive for a-SMA was less than 1% by immunocytochemistry, indicating the purity of the cell population as Kupffer cells to be more than 99% (data not shown). The purity of the isolated Kupffer cells was comparable to that in the previous report (Kitani et al, 2011(Kitani et al, , 2014.…”
Section: Resultssupporting
confidence: 84%
“…For the immunocytochemical characterization, we used a series of antibodies that detect cell-type specific marker proteins of liver cells as described in Table 1. Primary BKC exhibited a macrophage-like morphology, as previously reported by Kitani et al (2011Kitani et al ( , 2014. In addition, the isolated BKC were strongly positive for CD11b, CD172a, and MHC-II; weakly positive for CD14 and CD68; but negative for CD11c ( Figure 1A).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These cells represent approximately 10-15% of all liver cells. Kupffer cells attack blood-borne particles, whereas other macrophages serve in immune surveillance [28]. Dermal macrophages and Langerhans cells take up residence in the skin.…”
Section: Macrophagesmentioning
confidence: 99%
“…A previous study showed the functional expression of P2X7R in swine ovarian theca cells [9] . In this study, to understand the role of P2X7R in the innate immune defense of swine, we aim to study the expression and function of P2X7R in swine macrophages, which were obtained from mixed primary cultures of swine kidney or liver tissues [10] . Despite the presence of P2X7R mRNA and protein, extracellular ATP failed to induce P2X7R-dependent cellular responses in the swine macrophages.…”
Section: Introductionmentioning
confidence: 99%